2018
DOI: 10.1002/da.22861
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of depression‐related phenotypes with cardiometabolic risks: Polygenic analyses and exploring shared genetic variants and pathways

Abstract: Background: Numerous studies have suggested associations between depression and cardiometabolic (CM) diseases. However, little is known about the mechanism underlying this comorbidity, and whether the relationship differs by depression subtypes.Methods: Using polygenic risk scores (PRS) and linkage disequilibrium (LD) score regression, we investigated the genetic overlap of various depression-related phenotypes with a comprehensive panel of 20 CM traits. GWAS results for major depressive disorder (MDD) were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 68 publications
(92 reference statements)
3
32
1
1
Order By: Relevance
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic etiology between MDD and type 2 diabetes based on both PRS and genetic correlations (Clarke et al, 2016;Kan et al, 2016;Wong et al, 2019).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Twin studies have previously shown genetic overlap between MDD and type 2 diabetes, but evidence from genetic studies has been weaker. The current study, however, does show evidence for a shared genetic etiology between MDD and type 2 diabetes based on both PRS and genetic correlations (Clarke et al, 2016;Kan et al, 2016;Wong et al, 2019).…”
Section: Discussioncontrasting
confidence: 84%
“…Studies using twin data also showed that the phenotypic association between MDD and type 2 diabetes was partly due to genetic effects (Kan et al, 2016). This finding has been replicated using a polygenic risk score approach (Wong et al, 2019), but not using genetic correlations (Clarke et al, 2016;Wong et al, 2019). The Brainstorm Consortium did not find a significant genetic correlation between MDD and stroke (Anttila et al, 2018), while Wassentheil-Smoller et al (Wassertheil-Smoller et al, 2018) showed that higher polygenic risk for MDD was associated with increased risk for stroke, in particular small vessel disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings for other cardio-metabolic traits have been inconsistent. Previous studies have identified genetic overlap between MDD and BMI using polygenic risk scores (19), but not based on genetic correlations (20). However, more recent GWAS studies now have the power to detect a genetic correlation between MDD and BMI (14).…”
Section: However It Remains Unclear To What Extend These Mechanisms mentioning
confidence: 99%
“…In addition to the above, sometimes a protein whose level changes as a result of a disease may yet be a risk factor for another condition. For example, depression is associated with increased risk of cardiometabolic disorders 9 , and some have postulated inflammatory pathways and proteins as mediating factors 10,11 .…”
Section: Introductionmentioning
confidence: 99%